Socio-demographic distribution of hypertension and its risk factors among urban slum adults of Tirupati: a cross sectional study - Deekala, Ravi Sankar; G., Ravi Prabhu; R., Altaf Hussain; Kadari, Saritha (International Journal Of Community Medicine And Public Health, 2017)
Background: Some of the community surveys have documented that between three and six decades, prevalence of hypertension has increased by about 30 times in urban people and by about 10 times among the rural area people. Urban population of developing countries is showing similar prevalence to that of developed countries. Treating hypertension has been associated with 15% reduction in incidence of myocardial infarction and 40% reduction of stroke. The objectives of the study were to estimate the prevalence of hypertension among adults aged between 30-50 years in selected urban slum areas of Tirupati and to know the associated important risk factors with hypertension in the study subjects. Methods: A community based cross sectional study was conducted in urban slum community of Tirupati, to estimate the prevalence and its risk factors of Hypertension by using the JNC VII criteria. This study was conducted during January 2012 to February 2013, among 2136 subjects of 30-50 years age group. Results: The prevalence of hypertension was found 481 (22.5%), majority of them belongs to the age group of 45-50 years 212 (44.0%) and lowest in 30-35 years 45 (9.3%). Hypertension was predominant in males 186 (30.1%) than females 295 (19.4%). Conclusions: This study found that there is increasing trend of prevalence of hypertension in the urban community. This study suggests to health planners to take remedial measures to address growing hypertension in the community through health education about lifestyle changes, dietary modification, and avoidance of stress.